Motivation and Academic Performance of Secondary Students in Science: A Correlational Study - Sabanal, Germie Joy A.; Reputana, Keziah Grace D.; Palwa, Sharene S.; Labandero, Catherine Lolinette H.; Alimbon, Jemer A. (Universitas Syiah Kuala, 2023)
Motivation theories have suggested that motivation and academic performance are positively related. While many studies worldwide have explored this relationship, investigation in the Philippine educational setting remains scarce. Hence, this study described the levels of students motivation towards learning and academic performance in science and determined whether a significant relationship existed between these variables. Employing a correlational research design, this study surveyed 318 secondary students in a private, diocesan school in Davao del Norte, Philippines. Mean, standard deviation, and Pearson r were used to analyze the data. Results showed students motivation towards learning was generally high, and their academic performance was very satisfactory. Among the factors considered for motivation, only performance goal posted a moderate level, while other aspects, such as achievement goal, active learning strategies, learning environment stimulations, science learning value, and self-efficacy, registered high levels. Furthermore, this study revealed the students motivation towards learning and academic performance were positively and significantly correlated. While this study already found high motivation and very satisfactory academic performance among students, the researchers still recommend raising them to very high and outstanding levels, respectively. Further research on this topic with a more representative sample is highly recommended. Using other constructs to relate to any of the variables is also encouraged